2002
DOI: 10.1093/her/17.4.451
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity intervention: a Transtheoretical Model-based intervention designed to help sedentary young adults become active

Abstract: Physical activity levels in young adults are low. Research supports the use of the Transtheoretical Model of behaviour change (TM) in designing physical activity interventions. This study used a pre-post randomized control design to investigate the effectiveness of a self-instructional intervention for helping sedentary young adults to initiate physical activity. Post-intervention, significantly more of the experimental group (80%), in comparison to the control group (68%), improved their exercise stage of cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 28 publications
7
66
0
3
Order By: Relevance
“…Consequently, the physical activity interventions using the TTM, attempt to match the intervention materials and strategies to a person's stage of change. Generally speaking, research has shown that participants who receive TTM interventions matched to their stage of change, progress more towards the action and maintenance stages, than participants in control groups, who receive no treatment, or standard health care (Blissmer & McAuley, 2002;Dallow & Anderson, 2003;Fahrenwald, Atwood, Walker, & Johnson, 2004;Goldstein et al, 1999;Kim, Hwang, & Yoo, 2004;Kirk, Mutrie, McIntyre, & Fisher, 2004;Pinto et al, 2002;Woods, Mutrie, & Scott, 2002).…”
Section: Transtheoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the physical activity interventions using the TTM, attempt to match the intervention materials and strategies to a person's stage of change. Generally speaking, research has shown that participants who receive TTM interventions matched to their stage of change, progress more towards the action and maintenance stages, than participants in control groups, who receive no treatment, or standard health care (Blissmer & McAuley, 2002;Dallow & Anderson, 2003;Fahrenwald, Atwood, Walker, & Johnson, 2004;Goldstein et al, 1999;Kim, Hwang, & Yoo, 2004;Kirk, Mutrie, McIntyre, & Fisher, 2004;Pinto et al, 2002;Woods, Mutrie, & Scott, 2002).…”
Section: Transtheoretical Modelmentioning
confidence: 99%
“…What is less clear is whether these mediators are related to a precise stage of change, and whether it is important to match the intervention to the stage of change. Although stage-matched interventions perform better when compared with a control condition (Blissmer & McAuley, 2002;Dallow & Anderson, 2003;Fahrenwald et al, 2004;Goldstein et al, 1999;Kim et al, 2004;Kirk et al, 2004;Pinto et al, 2002;Woods et al, 2002), research comparing stage-matched with stage mismatched, or other social cognitive interventions, is more equivocal. Gerda and Brian Winfried (2005) compared the progression in exercise stage of change in participants who had received a stage-matched intervention, including physician feedback and stage-matched leaflets, with participants who only received physician feedback.…”
Section: Ttm and Physical Activity Interventionsmentioning
confidence: 99%
“…Subjects were asked to show which options best described their current level of PA (walking, biking, or playing ball for 30 minutes or more, 5 days a week). regularly active for more than 6 months (maintenance), regularly active for the last 6 months(action),action irregularly active and intention (preparation), sedentary and 6-month intention (contemplation), sedentary, no intention (pre-contemplation) (19). SE: SE was measured using the ESE scale developed by Bandura (20).…”
Section: Discussionmentioning
confidence: 99%
“…In light of the poor results obtained in the interventions mentioned above and because the integration of stages and processes of change can provide a beneficial guide for PA interventions (11), it would seem that adding the processes of change to PA interventions would be useful in increasing their effectiveness. Therefore, this study was designed to evaluate the effects of a TTM-based intervention on the PA of patients with HTN.…”
Section: Objectivesmentioning
confidence: 99%
“…One of the most common theoretical frameworks used for understanding health behaviour change is the trans-theoretical model (TTM) (8) which indicates that individuals engaging in a new behavior move through a series of stages of change (9). These stages include: pre-contemplation (inactive, no intention), contemplation (inactive and 6-month intention), preparation (irregularly active and intention), action (regularly active for less than 6 months) and maintenance (regularly active for more than 6 months) (10,11). Processes of change are strategies that people use to progress through stages.…”
Section: Introductionmentioning
confidence: 99%